PATIENT SATISFACTION WITH QUALITY AMONG TYPE 2 DIABETES PATIENTS AT PUSKESMAS LEMPAKE IN 2025 - Zulhazmi, Rafi Ahza; Bakhtiar, Rahmat; Isnuwardana, Ronny (HEARTY, 2026)
Rising prevalence and number of diabetic patients worldwide pose challenges for treatment success due to the chronic nature of diabetes itself. Evaluating healthcare service quality is important to ensure treatment continuity for chronic disease management, especially for Type 2 Diabetes Mellitus (T2DM). This research was conducted from August through October 2025, with a total of 60 respondents. The instrument used in this research was SERVQUAL, measuring five dimensions (Reliability, Responsiveness, Assurance, Empathy, and Tangibles) with analysis of each dimension’s gap between patients’ expectations and perceptions. The results showed most respondents (66.67%) were satisfied with the services provided. However, the overall gap revealed negative values across all dimensions, indicating that patients’ expectations were not fully met. The widest gaps were found in Tangibles (-0.11) and Reliability (-0.11) dimensions, specifically about physical infrastructure and service accuracy. Meanwhile, Assurance and Empathy were dimensions with the smallest gaps (-0.05), reflecting high trust in medical personnel and their attitude. Although the majority of T2DM patients are satisfied, gaps in service quality remain, especially in physical evidence and reliability. Improvements should be made with infrastructure maintenance and internal evaluation for the Prolanis implementation to further enhance patient experience.